PENGARUH CORPORATE IMAGE, STORE ATMOSPHERE DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (Studi pada pelanggan Aluna Home Spa Semarang) - Nadya Agustina Budi; Bambang Sutedjo (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This study aims to determine and analyze the effect of corporate image, store atmosphere on customer satisfaction and its impact on customer loyalty. The population is customers from Aluna Home Spa, with a sample of 100 respondents. The data testing technique used in this study uses a validity test with a loading factor, a reliability test with Cronbach's alpha and multiple regression analysis. The results of the study show that corporate image has a positive effect on customer satisfaction, store atmosphere has a positive effect on customer satisfaction and customer satisfaction has a positive effect on customer loyalty